The Effect of Nurses' Anxiety Levels About Covid-19 Transmission on Nurse-to-Patient Caring Behavior In the Inpatient Room - Riya Anita Candra, Vania; Heri Susanti, Indri; Tri Yudono, Danang (Institute Of Computer Science (IOCS), 2024)
Nurses' caring behavior is important for patients as service recipients so that it improves the patient's own recovery. Disturbances caused by caregiver anxiety can interfere with caregiver performance. The purpose of this study was to determine the effect of the anxiety level of nursing before the transmission of Covid-19 on nursing behavior in hospital patients. This type of study is a library search with a literature search design. The search strategy to obtain journals used the keywords